2018
DOI: 10.1111/aji.13023
|View full text |Cite
|
Sign up to set email alerts
|

New insights into the efficacy of SR‐16234, a selective estrogen receptor modulator, on the growth of murine endometriosis‐like lesions

Abstract: SR has a regressive effect on the development of murine endometriosis-like lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 39 publications
(76 reference statements)
0
8
0
Order By: Relevance
“…After one daily administration of bazedoxifene/conjugated estrogens for 12 weeks, all subjects demonstrated an LH surge without endometrial alterations or abnormal ovarian folliculogenesis [79]. Khine et al evaluated the effects of SR-16234 on murine endometriosis-like lesions [80]. SR-16234 is a SERM which was reported to have ERα-antagonistic activity with a weak partially agonist activity to the ERβ receptor.…”
Section: Treatments and Innovations In Clinical Management Related To Ersmentioning
confidence: 99%
“…After one daily administration of bazedoxifene/conjugated estrogens for 12 weeks, all subjects demonstrated an LH surge without endometrial alterations or abnormal ovarian folliculogenesis [79]. Khine et al evaluated the effects of SR-16234 on murine endometriosis-like lesions [80]. SR-16234 is a SERM which was reported to have ERα-antagonistic activity with a weak partially agonist activity to the ERβ receptor.…”
Section: Treatments and Innovations In Clinical Management Related To Ersmentioning
confidence: 99%
“…Another recent study suggested dual targeting of ERα with tamoxifen and ERRα with XCT790 may be beneficial for EC treatment, but this requires further validation (Mao et al 2019). While administration of SERMs/SERDs may be appropriate for postmenopausal women with cancer, their use in younger women with non-malignant endometrial disorders such as endometriosis is more challenging with data limited to promising results in preclinical models (Kulak et al 2011, Khine et al 2018. The observation that ERβ is highly expressed in endometriosis lesions and the development of ERβ-selective agonists such as ERβ-041 with apparent anti-inflammatory properties provided a rationale for testing them as therapies for endometriosis with promising results obtained in preclinical models (Harris 2006).…”
Section: Targeting Oestrogen Receptors In Endometrial Disordersmentioning
confidence: 99%
“…BALB/c mouse model [36] INT-777 Suppresses TGR5/TNFα/NF-κB pathway in endometriotic cells. hESCs isolated from patients with endometriosis [116] Niclosamide Inhibits macrophage-induced inflammation and endometriotic cell viability partly via suppressing NF-κB signaling.…”
Section: Preclinical Drugs For Blocking Nf-κb Signaling In Endometriosismentioning
confidence: 99%
“…SR-16234 is a selective estrogen receptor modulator that has potent antagonistic activity on ERα with weak partial agonist activity against the ERβ receptor 36 . In a BALB/c mouse model of endometriosis, treatment with SR-16234 substantially decreased NF-κB p65 expression and reduced the growth of endometriotic lesions 36 .…”
Section: Regulation Of Nf-κb Signaling In Endometriosismentioning
confidence: 99%
See 1 more Smart Citation